Phase Ib/II study of weekly topotecan and daily gefitinib in patients with platinum resistant ovarian, peritoneal, or fallopian tube cancer. Issue 11 (9th October 2020) - Chelariu-Raicu, Anca; Levenback, Charles F; Slomovitz, Brian M; Wolf, Judith; Bodurka, Diane C; Kavanagh, John J; Morrison, Christopher; Gershenson, David M; Coleman, Robert L
Abstract : Introduction: 50–70% of epithelial ovarian cancers overexpress epidermal growth factor receptor, and its expression has been correlated with poor prognosis. We conducted a phase Ib/II trial to examine the efficacy, safety, and toxicity of gefitinib, a tyrosine kinase inhibitor, combined with topotecan in women with recurrent ovarian cancer with epidermal growth factor receptor positivity. Methods: Patients with measurable recurrent or persistent cancer after treatment with a platinum containing regimen with positive epidermal growth factor receptor expression, as determined by immunohistochemistry, were eligible for the study. Initial treatment was 250 mg/day gefitinib (oral) and 2.0 mg/m 2 topotecan (intravenous) on days 1, 8, and 15, on a 28 day cycle. Dose escalations were planned for topotecan (dose levels 1–3: 2, 3, and 4 mg/m 2 ) until the maximum tolerated dose was reached. Results: 19 patients received a total of 61 cycles. Median age was 59.8 years (range 42–76 years). Histologic types in treated patients included 74% serous (n=14), 11% mixed (n=2), 11% transitional (n=2), and 5% clear cell (n=1). For phase Ib, three patients were treated at dose level 1, three at dose level 2, and three at dose level 3 for topotecan. The maximum tolerated dose was 4.0 mg/m 2 (days 1, 8, and 15) for topotecan and 250 mg (daily) for gefitinib. Therefore, dose level 3 was used for phase II. Among the 19 patients, 63.2% (n=12) had progressive disease, 15.8% (n=3) had stable disease, 10.5% (n=2) had a partial response, and 10.5% (n=2) were not evaluable. The most serious adverse events of any grade attributed to the therapy were anemia (89.4%), neutropenia (68.4%), abdominal pain (84%), constipation (78.9%), and diarrhea (78.9%). Conclusion: Although the drug combination was relatively well tolerated, this prospective phase Ib/II clinical trial did not show sufficient clinical activity of topotecan combined with gefitinib in patients with epidermal growth factor receptor positive recurrent ovarian, fallopian tube, or peritoneal cancers.